Glucocorticoid action in human corneal epithelial cells establishes roles for corticosteroids in wound healing and barrier function of the eye. (November 2016) - Kadmiel, Mahita; Janoshazi, Agnes; Xu, Xiaojiang; Cidlowski, John A.
Abstract: Glucocorticoids play diverse roles in almost all physiological systems of the body, including both anti-inflammatory and immunosuppressive roles. Synthetic glucocorticoids are one of the most widely prescribed drugs and are used in the treatment of conditions such as autoimmune diseases, allergies, ocular disorders and certain types of cancers. In the interest of investigating glucocorticoid actions in the cornea of the eye, we established that multiple cell types in mouse corneas express functional glucocorticoid receptor (GR) with corneal epithelial cells having robust expression. To define glucocorticoid actions in a cell type-specific manner, we employed immortalized human corneal epithelial (HCE) cell line to define the glucocorticoid transcriptome and elucidated its functions in corneal epithelial cells. Over 4000 genes were significantly regulated within 6 h of dexamethasone treatment, and genes associated with cell movement, cytoskeletal remodeling and permeability were highly regulated. Real-time in vitro wound healing assays revealed that glucocorticoids delay wound healing by attenuating cell migration. These functional alterations were associated with cytoskeletal remodeling at the wounded edge of a scratch-wounded monolayer. However, glucocorticoid treatment improved the organization of tight-junction proteins and enhanced the epithelial barrier function. Our results demonstrate that glucocorticoids profoundly alter corneal epithelial gene expression and many of these changes likely impact both wound healing and epithelial cell barrier function. Highlights: Functional glucocorticoid receptors are expressed in mouse corneas. Glucocorticoids regulated over 4000 genes in human corneal epithelial cells. Glucocorticoids enriched genes associated in wound healing processes. Glucocorticoids decreased cell migration rate but enhanced epithelial integrity.